Aging induces T cells with distinct transcriptomic profiles and functions in brain-associated tissues - Si, Youwen; Zhang, Yuanyue; Yang, Qi (Frontiers in Immunology, 2025)
BackgroundAging is known to induce the emergence of distinct lymphocyte populations with unique molecular and functional characteristics. However, the impact of aging on the transcriptomes and functional activities of CD4 and CD8 T cells in non-lymphoid tissue remains poorly understood. Investigating aging-induced transcriptomic changes in tissue-infiltrating immune cells may provide insights into tissue homeostasis and malignancy in the aging context.MethodsSingle-cell RNA sequencing (scRNA-seq) was performed to compare the cell subsets and transcriptomes of CD4+ and CD8+ T cells in brain-associated tissue, including the meninges and choroid plexus of young and aged mice. Flow cytometry was used to analyze aging-associated CD4+ T cells in the hippocampus. Depletion antibodies were employed to investigate the functional role of aging-associated T cells.ResultsAging induces a shift in the transcriptomes of CD4+ and CD8+ T cells in the meninges and choroid plexus toward an effector memory phenotype. In aged mice, T helper 2 (Th2) cells, regulatory T cells (Tregs), and distinct subsets of CD153-expressing CD4+ T cells accumulate in these brain-associated regions. Notably, CD153-expressing CD4+ T cells also infiltrate the hippocampus. Depletion of CD153+ cells using anti-CD153 antibodies leads to impaired cognitive function, suggesting a potential protective role for these cells in the aging brain.ConclusionsAging alters the transcriptome of brain-associated CD4+ and CD8+ T cells. In particular, distinct CD153-expressing CD4+ T cells accumulate in the meninges and choroid plexus, and also infiltrate the hippocampus during aging. These cells may play a protective role in maintaining brain homeostasis.